Serous Adenoma of the Pancreas With Multiple Microcysts Communicating With the Pancreatic Duct. Issue 1 (1998) - Samel, S.; Horst, F.; Becker, H.; Brinck, U.; Schwörer, H.; Ramadori, G.; Oestmann, J.-W.
Abstract : The rare neoplastic cystic adenomas of the pancreas form two groups of tumors: macrocystic mucinous and microcystic serous adenomas. Both entities show specific radiologic and histologic features. Several recent case reports, however, suggest some diversity within the group of microcystic serous adenomas. We present the case of a young man operated because of epigastric pain for 12 months and a palpable microcystic tumor of the pancreatic head. Multiple cysts communicating with branches of the pancreatic duct in an alveolar-like pattern were demonstrated on endoscopic retrograde cholangiopancreatography. Histologic examination of the specimen confirmed the diagnosis of a serous adenoma of the pancreas. The tumor morphology in this case may suggest a ductal origin of microcystic serous adenomas.